MOBILE MONEY SYSTEM AS A TOOL OF FINANCIAL EMANCIPATION OF THE POOREST OF THE POOR IN DEVELOPMING COUNTRIESM - Chmielewski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
This article uses an examination of M-PESA, a large-scale financial service in Kenya, that is accessible from ordinary mobile phones. It has seen exceptional success since its introduction by mobile phone operator Safaricom in Kenya in March 2007 - it has already been adopted by 17 million customers. In this article M-PESA’s market success is  interpreted in the context of fight against poverty in developing countries. An innovational tool that has been introduced by mobile platform removes barrier to financial inclusion of the poorest of the poor and links them with conventional bank sector. Once poor people have access to cost-effective electronic means of payments such as M-PESA, they could, in principle, be profitably marketable subjects by a range of financial institutions.